Wayfinding during a wildfire evacuation. Issue 3 (24th December 2019) - Brachman, Micah L.; Church, Richard; Adams, Benjamin; Bassett, Danielle
Abstract : Purpose: Emergency evacuation plans are often developed under the assumption that evacuees will use wayfinding strategies such as taking the shortest distance route to their nearest exit. The purpose of this paper is to analyze empirical data from a wildfire evacuation analyzed to determine whether evacuees took a shortest distance route to their nearest exit and to identify any alternate wayfinding strategies that they may have used. Design/methodology/approach: The wildfire evacuation analysis presented in this paper is the outcome of a natural experiment. A post-fire online survey was conducted, which included an interactive map interface that allowed evacuees to identify the route that they took. The survey results were integrated with several additional data sets using a GIS. Network analysis was used to compare the routes selected by evacuees to their shortest distance routes, and statistical hypothesis testing was employed to identify the wayfinding strategies that may have been used. Findings: The network analysis revealed that 31 percent of evacuees took a shortest distance route to their nearest exit. Hypothesis testing showed that evacuees selected routes that had significantly longer distances and travel times than the shortest distance routes, and indicated that factors such as the downhill slope percentage of routes and the elevation of exits may have impacted the wayfinding process. Research limitations/implications: This research is best regarded as a spatiotemporal snapshot of wayfinding behavior during a single wildfire evacuation, but could inspire additional research to establish more generalizable results. Practical implications: This research may help emergency managers develop more effective wildfire evacuation plans. Originality/value: This research presents an analysis of an original data set that contributes to the broader body of scientific knowledge on wayfinding and spatial behavior during emergency evacuations.